Effects of internal cooling on physical performance, physiological and perceptional parameters when exercising in the heat: A systematic review with meta-analyses - Heydenreich, J.; Koehler, K.; Braun, H.; Grosshauser, M.; Heseker, H.; Koenig, D.; Carlsohn, A. (Frontiers in Physiology, 2023)
Background: An elevated core temperature (Tcore) increases the risk of performance impairments and heat-related illness. Internal cooling (IC) has the potential to lower Tcore when exercising in the heat. The aim of the review was to systematically analyze the effects of IC on performance, physiological, and perceptional parameters.